A Exploração de recursos faunísticos na Amazônia: história, economia e meio ambiente (do Brasil Colônia ao Império) - SOUSA, Girlian Silva de (Universidade Federal do Pará, 2024)
This work aims to analyze the insertion of the Amazon economy into commercial capitalism based on faunal extractivism in the period from 1759 to 1830, which comprises the stage of conquest and consolidation of the territory. To this end, the process of producing data relating to faunal extractivism in the Brazilian Amazon during the time frame established, the participation of faunal extractivism in the dynamics of Brazil's insertion into mercantilism, the Portuguese colonizing model in the Brazilian Amazon, and finally, the role of faunal extractivism in the insertion of the Amazon Valley into the dynamics of mercantile capitalism, from the perspective of the organization of the workforce. The originality of this documentary research is evident in the volume and extent of the collection consulted, the length of the time frame, the scope of the territorial scope, and the diversity and volume of faunal resources researched, which encompasses Amazon turtle fishing and collecting eggs, fishing for manatee, arapaima and mullet. As a novelty, the use of alligator oil for lighting and as an ingredient in mortar compounds for buildings. The topic is approached from a heterodox theoretical basis, which allows discussing the Portuguese administrative model in the Brazilian Amazon, the mechanisms of subordination of the colony to metropolitan power, vicissitudes and influences in contemporary Brazilian society. The issue of the mode of production via compulsory labor and the mechanisms for appropriating indigenous technology is used as a canvas for the discussion about the centrality of faunal extraction for the colonization of the territory. The relative silence of economic historiography regarding the centrality of activities that enabled the production of products considered central in the study via economic cycles is questioned. As a strategy, this work provides a brief histographic review of the first economic activities carried out in Brazil – the trade in human beings and fauna. The results reveal, in summary, that without indigenous technology, which includes the knowledge that enabled faunal extraction, it would have been impossible for the Portuguese conquerors to consolidate their dominance over the territory and enable economic activities aimed at meeting the demands of the external market.